Topological N-glycosylation and site-specific N-glycan sulfation of influenza proteins in the highly expressed H1N1 candidate vaccines - She, Yi-Min (Sci Rep, 2017)
The outbreak of a pandemic influenza H1N1 in 2009 required the rapid generation of high-yielding vaccines against the A/California/7/2009 virus, which were achieved by either addition or deletion of a glycosylation site in the influenza proteins hemagglutinin and neuraminidase. In this report, we have systematically evaluated the glycan composition, structural distribution and topology of glycosylation for two high-yield candidate reassortant vaccines (NIBRG-121xp and NYMC-X181A) by combining various enzymatic digestions with high performance liquid chromatography and multiple-stage mass spectrometry. Proteomic data analyses of the full-length protein sequences determined 9 N-glycosylation sites of hemagglutinin, and defined 6 N-glycosylation sites and the glycan structures of low abundance neuraminidase, which were occupied by high-mannose, hybrid and complex-type N-glycans. A total of ~300 glycopeptides were analyzed and manually validated by tandem mass spectrometry. The specific N-glycan structure and topological location of these N-glycans are highly correlated to the spatial protein structure and the residential ligand binding. Interestingly, sulfation, fucosylation and bisecting N-acetylglucosamine of N-glycans were also reliably identified at the specific glycosylation sites of the two influenza proteins that may serve a crucial role in regulating the protein structure and increasing the protein abundance of the influenza virus reassortants.